Effect of Project Based Learning (PJBL) Learning Model on Learning Outcomes Shooting Basketball - Exkwantri Exkwantri; Fitriana Puspa Hidasari; Novi Yanti (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
Lack of students' ability to master the shooting basketball, making shooting inaccurate towards the hoop. It is necessary to apply the right learning model to improve students' abilities in shooting. The purpose of this study was to see the impact of project basic learning on shooting skills in basketball games. The research method used is an experiment with quantitative data types. The population in this study were class XI students at SMKN 3 Pontianak. Sampling used a purposive sampling technique and obtained a sample of 35 students. Based on the research conducted, the results obtained were an average pretest score of 10.5 while a posttest average score of 14.0 with an average increase difference of 3.5 or 33.33%. For data analysis in research used t-test. The results of the t-test calculations show that there is a significant effect between the pre-test and the post-test. The significance value obtained is 0.000, less than 0.05. As for the test that was carried out, the result was that tcount (16.557) > ttable (2.035). From these results it can be seen that Ha is accepted and H0 is rejected, which means that the project based learning model influences the ability to shoot basketball in class XI students at SMKN 3 Pontianak.